Jovens rurais, corações urbanos: jornal nacional e as desigualdades sociais do campo - Schnorr, Julia Mello (2013)
This is an ethnographic reception study of Jornal Nacional conducted with six young people from the countryside, in the central area of Rio Grande do Sul. Three of them currently live in urban areas, and the others three live in the countryside, where they maintain daily contact with towns. The study aims to investigate how rural youth linked to social movements interpret media representations concerning ruralities offered by Jornal Nacional, especially related to rural residents and their living space and labor, to rural social movements, and to pesticides and transgenic. We want to understand how this interpretation reflects on their identities. The youth from the working class have a relationship with organized civil society through social movements and organizations with critics to the status quo of the landlord organization and of agricultural production in the country. A group is formed by settlers from the areas conquered by the Movement of Landless Rural Workers (MST), the other is organized through networks of Solidarity Economy in the project Esperança/Cooesperança and in the Cooperativa Central de Desenvolvimento Rural (Coopercedro). Methodologically, we have articulated the critical ethnography reception, the life history interviews, the Theory of Mediation by Martin-Barbero, and the Encoding/Decoding Model by Stuart Hall with works by Ronsini et al. (2009). From the analysis, we consider that part of youth identity presents a “rurban” (hybrid) identity, which draws their life projects interweaving the rural and urban areas as a result of new cultural boundaries (CARNEIRO, 2005). We noticed that young people who have had or still have family members close to social movements are those holding positions more resistant to media encodings. What is from the order of negotiation refers to the reception of themes like transgenic, use of pesticides, land reform and MST, topics in which social movement potentially focus on. We also found trading readings in media reception of the rural zone and of people who live in this space, especially from young people who do not see the field as a space with opportunities. The media readings are a result of class mediation, life history and family involvement in the social movement. We consider that the sample proves to be reflexive; they ponder the questions of survival and the desire to consume, not going to meet the individualism that thoughtlessly incorporates immediate solutions. We believe that having proximity with social movements does not guarantee by itself political involvement. Between staying and leaving the rural areas, young people range from fulfilling their personal and autonomous realization, typically by migrating to the city, to having an associative work with their families and life projects that encompass the urban and rural environments.